Adsorptive removal of Cr(VI) from aqueous solution onto different kinds of modified bentonites. Issue 1 (30th January 2014) - Zhang, Sen; Yang, Jian; Xin, Xiaodong; Yan, Liangguo; Wei, Qin; Du, Bin
<x xml:space="preserve">Abstract</x> Chromium(VI) removal is important for wastewater treatment, and adsorption is an efficient treatment process. In this paper, natural bentonite was exchanged to sodium bentonite (Na‐Bent) by adding NaCl. Hydroxy‐alumina pillared bentonite (OH‐Al‐Bent), octadecyltrimethylammonium chloride modified bentonite (OTMAC‐Bent) and organic‐inorganic pillared bentonite (OTMAC‐OH‐Al‐Bent) were prepared via exchange reaction and then characterized through FTIR and BET measuring. Batch experiments were conducted on adsorption of Cr(VI) by the prepared modified bentonites. The results showed that the adsorption of Cr(VI) by Na‐Bent and natural bentonite was neglected due to their weak adsorption performance. The adsorption capacity of Cr(VI) on OH‐Al‐Bent was much lower than on OTMAC‐Bent and OTMAC‐OH‐Al‐Bent. The adsorption isotherms of Cr(VI) by OTMAC‐OH‐Al‐Bent and OTMAC‐Bent both fit well with Freundlich and Langmuir adsorption model and the adsorption kinetics data of Cr(VI) fit well with the pseudo‐second‐order model. The adsorption efficiency was over 90%, suggesting that OTMAC‐OH‐Al‐Bent and OTMAC‐Bent were excellent adsorbents for effective Cr(VI) removal from aqueous solution. © 2014 American Institute of Chemical Engineers Environ Prog, 34: 39–46, 2015